Gh̳ana session with Manuel Sultana and Jimmy Camilleri and Wenzu Caruana in the Manuel Casha Maltese folklore music project - Sultana, Manuel; Camilleri, Jimmy; Caruana, Wenzu; Casha, Manuel, 1944- (1992)
Folkloric recording.
Gh̳ana (pronounced anah) is the Maltese term for folksong or sung poetry, within gh̳ana are a number of forms, amongst them are spiritu pront, which means quick thought and is the most well known, extemporised form of gh̳ana. Tal Fatt which means 'of fact' are long writtem poems telling of historical events and gh̳ana fil gholi sometimes called Bormliza (meaning in high voice)
Recorded on 26 November 1992 in Sunshine, Vic.
Also available online
Songs performed in Maltese.
Summary not yet available.
Keywords: Maltese Australians -- Music; Folk songs, Maltese; Poetry, Maltese